Defining Mononuclear Phagocyte Subset Homology Across Several Distant Warm-Blooded Vertebrates Through Comparative Transcriptomics - Vu Manh, Thien-Phong; Elhmouzi-Younes, Jamila; Urien, Céline; Ruscanu, Suzana; Jouneau, Luc; Bourge, Mickaël; Moroldo, Marco; Foucras, Gilles; Salmon, Henri; Marty, Hélène; Quéré, Pascale; Bertho, Nicolas; et al. (Frontiers in Immunology, 2015)
Mononuclear phagocytes are organized in a complex system of ontogenically and functionally-distinct subsets, that has been best described in mouse and to some extent in human. Identification of homologous mononuclear phagocyte subsets in other vertebrate species of biomedical, economic and environmental interest is needed to improve our knowledge in physiologic and physio-pathologic processes, and to design intervention strategies against a variety of diseases, including zoonotic infections. We developed a streamlined approach combining refined cell sorting and integrated comparative transcriptomics analyses which revealed conservation of the mononuclear phagocyte organization across human, mouse, sheep, pigs and, in some respect, chicken. This strategy should help democratizing the use of omics analyses for the identification and study of cell types across tissues and species. Moreover we identified conserved gene signatures that enable robust identification and universal definition of these cell types. We identified new evolutionarily conserved gene candidates and gene interaction networks for the molecular regulation of the development or functions of these cell types, as well as conserved surface candidates for refined subset phenotyping throughout species. A phylogenetic analysis revealed that orthologous genes of the conserved signatures exist in teleost fishes and apparently not in Lamprey, indicating conservation of the genetic support for mononuclear phagocyte organization throughout jawed vertebrates but likely not in agnathans. Altogether this work provides molecular clues to the definition and functions of mononuclear phagocyte subsets across vertebrates which shall be useful to rigorously identify these cells and to design universal strategies to manipulate them in many target species towards the goal to reach and maintain global health.